Kinerja Guru Dilihat Dari Spiritualitas, Komitmen Organisasi, Modal Psikologis, dan Perilaku Kewargaorganisasian - Imron, Imron (Sekolah Tinggi agama Islam Negeri (STAIN) Curup, 2016)
This article aims to determine the role of spirituality in improving teacher performance in terms of organizational commitment, psychological, and organizing behavior of teachers, which the teacher is in direct contact with students in the process of education and learning in schools. Spirituality is considered as a means to promote integrity, motivation and job satisfaction, and is considered a significant contribution to the success of their work. Someone who is guided by the spirituality that produces good moral habits and good nature were also more likely to be honest, loyal, trustworthy and have integrity. Through theories are constructed and formulated research paradigm, spirituality has a very significant role in influencing the performance of teachers through organizational commitment, psychological and organizing behavior. Keywords: Teacher Performance, Spirituality